Evaluasi Program Pertanian Ramah Lingkungan Berkelanjutan dalam Pengembangan Sentra Agribisnis Pangan di Kabupaten Ngawi (Studi Kasus Komoditas Padi) - Jaya, Dameydra; Daroini, Ahsin; Askafi, Eka (Universitas Islam Kadiri, 2024)
The Implementation of the Sustainable Environmentally Friendly Agriculture Program Policy in Kedunggalar District, Ngawi Regency is one of the rural development strategies to increase farmers' income, agricultural productivity, and investment in order to reduce tensions between urban and rural areas. Responding to these problems, this research was conducted to analyze sustainable environmentally friendly agricultural policy programs, determine strategies that support policy implementation, and encourage extension plans. This study uses a quantitative descriptive analysis method in which the purpose of purchasing programs is measured by Likert's Summated Rating (LSR) (T-score), SWOT analysis, and integrating Problem Centered and Local Government Policy. Based on the results of data analysis using the T-score obtained by respondents it can be said to be favorable (positive) and have an interest in the sustainability of the Sustainable Environmentally Friendly Agriculture Program in the development of Food Agribusiness centers in Kedunggalar District, Ngawi Regency. Strategies for developing food agribusiness, especially rice that can be carried out based on SWOT analysis are strategies for developing superior agricultural commodities, strategies for developing agricultural resources, strategies for developing agricultural infrastructure, strategies for developing public infrastructure, strategies for developing investment and marketing, and strategies for developing agricultural institutions. Meanwhile, based on the counseling design, what is needed is the manufacture of liquid organic fertilizer which is able to increase knowledge by 70.67% and is included in the effective criteria for programs and behavior change.